Bambangin Barasih: Transformasi Desa Pinggiran Sungai Melalui Konsep Zero Waste - Muhammad Huda Inayaturrahman; Ismar Hamid; Nurul Khairin Fadiya; Dewi Nuraini; M. Zakiyuddin Munziri; Siti Noor Ariani; Ahmad Riduan; Nor Aziziah (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2023)
Bambangin Village is a riverside village located on the Barito River in the Belawang Subdistrict, Barito Kuala Regency. In Bambangin Village, waste is a serious problem and a major concern for the community. 192 families (81.4%) choose to burn their household waste, and 44 families (18.6%) opt to dispose of waste in the river (Neo Hamid, 2022). This background led the service team to embark on a village transformation project with the concept of zero waste. The aim of this program is to address the waste problem and create an environmentally conscious community in Bambangin Village. The implementation method is based on intervention logic and an empowerment approach, which includes enabling, empowering, and protecting. The service activities are carried out in a live-in format, with the service team staying and actively engaging with the community for 37 days, from July 16 to August 21, 2023. The implemented activities include the activation of a waste bank, awareness campaigns on waste and its management, training on creative waste recycling, and eco-enzyme training. The culmination of these activities is the declaration of the village as waste-free by the head of Bambangin Village and a waste-free village parade by the community and all village officials. The village transformation with the zero-waste concept carried out by the service team has successfully brought about significant changes in the Bambangin Village community. This is evident in the cleaner physical environment of the village and the increased awareness of waste and the environment among the residents. This success is part of the process that has made Bambangin a 'BARASIH' village, where the community is empowered, the environment is pristine, friendly, natural, healthy, innovative, and harmonious. Designing a program based on social mapping and implementing a live-in approach is the key to the success of this service program.